Determinants of Nutritional Status in Toddlers - Nani Surtinah; Heru Santoso Wahito Nugroho; Suparji Suparji; Chitya Widya Ayu Raswati Desita (Humanistic Network for Science and Technology (HNST), 2021)
Nutritional status is a common problem for toddlers. Of the 129 toddlers there were 26 toddlers (20.2%) with underweight nutritional status, 102 toddlers (79.1%) with normal nutritional status and 1 toddler (0.7%) with very obese nutritional status in February 2019 in Randugede Village, Plaosan District. magnet. This study analysed the relationship between knowledge, income, education, parenting and nutrition status of children under five years of age. This kind of research is an analytical inquiry with a comprehensive approach. The research sample consisted of toddler and toddler mothers, all of whom accounted for 79 taken by simple random sampling. Data based on questionnaires and anthropometric measures of weight/size were compared to the z-score. Data analysis, both bivariate and multivariate. Based on the results of data analysis, it was found that the level of knowledge was p = 0.011, parents' income was p = 0.006, education level was p = 0.414, toddler's Dietary pattern was p = 0.010, and parenting pattern was p = 0.003. The results of the study can be concluded that there is a relationship between knowledge, income, dietary pattern, parenting and nutritional status of toddlers and there is no relationship between education and nutritional status of toddlers.Keywords: knowledge; income; education; Dietary pattern ary habits; parenting; nutritional status for toddler